Recent advancements review in zinc oxide and titanium dioxide saturable absorber for ultrafast pulsed fiber laser - Muhammad, Nur Ainnaa Mardhiah; Awang, Noor Azura; Basri, Hatijah (Elsevier, 2023)
Zinc oxide (ZnO) and titanium dioxide (TiO2) are classes of nanomaterials transition-metal oxides (TMOs) emerging as potential saturable absorption materials for ultrafast pulsed fiber lasers. In this review, we discussed the properties of these materials and the numerous preparation methods of ZnO and TiO2 materials-based saturable absorbers (SAs) with pros and cons. We also analyzed the incorporating method of SA. We provided an update on the growth of ultrafast pulsed fiber lasers based on ZnO and TiO2 as SA. Finally, the performance of the development of Q-switched and mode-locked fiber lasers based on ZnO and TiO2 as SA were addressed in the perspectives, and the uniqueness and challenges to provide insight for future improvement in pulse laser technology were also presented.